Imperio, constitución y diversidad en la América hispana - Annino, Antonio (El Colegio de México, A.C., 2008)
The many independences in Spanish America were rooted in an imperial crisis that upturned all the empire's territorial components, including Spain, in one single process, so that the breakup between the two Atlantic coasts was only one consequence  of a process mainly determined by a whole age. This paper argues that during  the emancipatory process,  the power  relations  between the many components of Spanish American  society changed to such a point that their reorganization within  the new constitutional models became very difficult. Thus, we should speak of the “legacy of the imperial crisis”, of the end of a whole world —not only a part of it: the Spanish American part—, to the point of rendering impossible the comparative approach implicit in the concept of “Atlantic revolutions”.